2021
DOI: 10.1002/anie.202012499
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Precise Preorganization of Open Metal Sites on Gold Nanoclusters with High Catalytic Performance

Abstract: Gold nanoclusters with surface open sites are crucial for practical applications in catalysis. We have developed a surface geometric mismatch strategy by using mixed ligands of different type of hindrance. When bulky phosphine Ph 3 P and planar dipyridyl amine (Hdpa) are simultaneously used, steric repulsion between the ligands will reduce the ligand coverage of gold clusters. A well-defined access granted gold nanocluster [Au 23 (Ph 3 P) 10 (dpa) 2 Cl](SO 3 CF 3) 2 (Au 23 , dpa = dipyridylamido) has been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 44 publications
1
74
0
Order By: Relevance
“…37,38 A second method often employed is by adding suitable auxiliary ligand, which has proved to be highly feasible in expanding structural and functional diversity, as exemplified by the two cases of [Au 32 (PPh 3 ) 8 (dpa) 6 ] 2+ and [Au 23 (PPh 3 ) 10 -(dpa) 2 Cl] 2+ (Hdpa = 2,2′-bipyridylamine) reported by the Wang group recently; the latter exhibits coordinatively unsaturated Au sites which endow it with potent catalytic activity. 39,40 On the other hand, given the wide commercial availability and easy tuning of the stereoelectronic property, phosphineprotected Au NCs are also good candidates for studying the ligand effects on the geometric and electronic structures of the metal cores, as well as their structure−property relationship. In this area, phosphine-protected chiral Au NCs are of special interest, and sustained efforts have been made to synthesize homochiral Au NCs and to study their chiroptical activities.…”
mentioning
confidence: 99%
“…37,38 A second method often employed is by adding suitable auxiliary ligand, which has proved to be highly feasible in expanding structural and functional diversity, as exemplified by the two cases of [Au 32 (PPh 3 ) 8 (dpa) 6 ] 2+ and [Au 23 (PPh 3 ) 10 -(dpa) 2 Cl] 2+ (Hdpa = 2,2′-bipyridylamine) reported by the Wang group recently; the latter exhibits coordinatively unsaturated Au sites which endow it with potent catalytic activity. 39,40 On the other hand, given the wide commercial availability and easy tuning of the stereoelectronic property, phosphineprotected Au NCs are also good candidates for studying the ligand effects on the geometric and electronic structures of the metal cores, as well as their structure−property relationship. In this area, phosphine-protected chiral Au NCs are of special interest, and sustained efforts have been made to synthesize homochiral Au NCs and to study their chiroptical activities.…”
mentioning
confidence: 99%
“…can activate CO as well as O 2 . Wang et al also reported the same results that Au 23 showed the excellent catalytic performance caused by eight uncoordinated gold sites on the metal nanoclusters surface 36. …”
mentioning
confidence: 63%
“…Moreover, due to ultrasmall size, the gold clusters can enter cell or injury site easily, resulting in high efficient treatment [26,28]. Gold clusters possess activities like SOD, CAT and GPx enzymes, performing significant antioxidant effects in TBI treatment [26,[28][29][30][31]. Though nanotechnologies for TBI diagnosis and monitoring were employed to promote the activity and utilization of nanozymatic biocatalysts like atom engineering, surface modification, and size modulation [32][33][34], it remains painless and chanllenged for clinical translation [12,15,[29][30][31][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Gold clusters possess activities like SOD, CAT and GPx enzymes, performing significant antioxidant effects in TBI treatment [26,[28][29][30][31]. Though nanotechnologies for TBI diagnosis and monitoring were employed to promote the activity and utilization of nanozymatic biocatalysts like atom engineering, surface modification, and size modulation [32][33][34], it remains painless and chanllenged for clinical translation [12,15,[29][30][31][35][36][37][38][39][40][41][42][43][44][45]. Different from the intravenous injection, the noninvasive diagnosis and stimulation for TBI can achieve rapid and painless treatment, worthy of considering to promote recovery and minimize disability.…”
Section: Introductionmentioning
confidence: 99%